PERANCANGAN APLIKASI PENGUKURAN PELAYANAN KEPUASAN MASYARAKAT PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MAJALENGKA BERBASIS WEB - Sumantri , Lugi; Susandi , Dony (Universitas Majalengka, 2025)
This study aims to design a web-based application for measuring public satisfaction with services at the Department of Communication and Informatics of Majalengka Regency. The background of this research is the absence of a structured system to measure and analyze the level of public satisfaction with public services, which limits community access and participation in providing feedback. The method used is the Rational Unified Process (RUP), which includes the stages of inception, elaboration, construction, and transition. The result of this research is a web-based application that enables the public to directly provide assessments of the services received, while the Department of Communication and Informatics can monitor survey results as a benchmark for improving service quality. The conclusion of this study is that the developed system is able to assist the public in submitting evaluations and facilitate the agency in managing satisfaction data, thereby enhancing transparency and the quality of public services.